(untitled) (Global Journal of Management and Business Research, 2016)
#x201C;You can#x2019;t manage what you don#x2019;t measure#x201D;; organisations are quantifying the capability of their manufacturing process to measure and manage #x2018;quality#x2019;. Six Sigma offer several tools, which helps measure the performance of a process. The process capability analysis is one such tool, which helps measure whether the process is proficient of producing consistent products that meet the standards. According to Dr Genichi Taguchi variability of the process has to be controlled even though the process is meeting all the specifications. Process capability analysis helps to reduce variability in the production processes. Process capability indices (PCIs) measure the capability of the process numerically. Process capability indices are used to explain a manufacturing process ability to produce items as per the voice of the customer (i.e. within the specified limits) and compare the intrinsic variability in a process with the customer#x2019;s design. Capability index is important, since it simplifies complex information about the process to a single unit less number.